Pengaruh Kebijakan Harga dan Service Quality Terhadap Keputusan Pembelian Jasa di Laundry Pondok Pesantren Riyadlul Jannah Mojokerto - Imam Wahyudi (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2022)
The purpose of this study was to analyze the effect of price policy and service quality on service purchase decisions at the laundry of the Riyadlul Jannah Islamic Boarding School Mojokerto. The sampling technique used in this research is purposive sampling. The data collection method used is a questionnaire. The data in this study were obtained from the results of distributing research questionnaires about price policy and service quality and purchasing decisions for service products to 70 respondents. The data analysis techniques used are instrument validity and reliability, classical assumption test, and multiple linear regression using the IBM SPSS Statistics 24 application. The results show that (1) the price policy variable has a positive and significant effect on service purchasing decisions and (2) the service quality variable has a positive and significant effect to the decision to purchase services.